Geographical perspectives on epidemic transmission of cholera in Haiti, October 2010 through March 2013 - Smallman-Raynor, Matthew; Cliff, Andrew; Barford, Anna (Taylor & Francis, 2015)
The current epidemic of El Tor cholera in the Caribbean republic of Haiti is one of the largest single outbreaks of the disease ever recorded. The prospects are that the epidemic will continue to present challenges to workers in public health medicine, epidemiology and allied fields in the social sciences for years to come. This article introduces geographers to the environmental context of the Haiti cholera epidemic, the principal data sources available to analyze the occurrence of the epidemic, and evidence regarding its geographical origins and dispersal during the first thirty months of the epidemic, October 2010–March 2013. Using weekly case data collated by the Haitian Ministère de la Santé Publique et de la Population (MSPP), techniques of time series analysis are used to examine inter- and intra-departmental patterns of cholera activity. Our analysis demonstrates a pronounced lag structure to the spatial development of the epidemic (Artibonite and northern departments  Ouest and metropolitan Port-au-Prince  southern departments). Observed variations in levels of epidemiological integration, both within and between departments, provide new perspectives on the spatio-temporal evolution of the epidemic to its March 2013 pattern.